TAX AVOIDANCE AND FINANCIAL PERFORMANCE OF NON-FINANCIAL QUOTED COMPANIES: EMPIRICAL EVIDENCE FROM MOROCCO - Каутар Лахрарі; Сіхам Сахбані (Фінансово-кредитна діяльність: проблеми теорії та практики, 2025)
The purpose of this article is to examine the relationship between tax avoidance (TA) and the financial performance (FP) of non-financial companies listed on the Moroccan stock exchange. FP is measured by a widely recognized accounting indicator which is the return on assets (ROA). TA is measured by the effective tax rate (ETR), a key indicator for assessing tax practices. This study uses a quantitative methodology based on the analysis of secondary data collected from the financial reports published by 32 non-financial companies listed on the Casablanca Stock Exchange (CSE). The analysis period spans five consecutive years, from 2018 to 2022. The generalized least squares (GLS) regression method was used to examine whether the relationship between TA and FP is significant. Indeed, the ETR exhibits an inverse relationship with TA, as a higher ETR corresponds to a lower TA. The results of this study reveal that the relationship between corporate TA and FP is significantly positive. Given that most research on the relationship between TA and FP focuses on Chinese, American and Australian companies, conducting research in new regions with different regulations could lead to different results. In this respect, the Moroccan context, characterized mainly by increased digitization of tax administration, the diversity of tax benefits accorded to certain priority sectors, the global economic disruption caused by the Covid-19 pandemic and the fiscal stimulus measures taken by the authorities during this crisis, represents a new context for studying the relationship between TA and FP.